Tasks Development for English Online Learning at SMA Negeri 4 Singaraja - Sumadi, Gde Dody; Saputra, I Nyoman Pasek Hadi; Agustini, Dewa Ayu Eka (STKIP AGAMA HINDU SINGARAJA, 2022)
Covid-19 pandemic is a situation that has impacted people’s life and all sectors especially Education. This pandemic situation forced the restrictions to do online learning in the teaching activities, including English learning in giving English Online Tasks. It raises pro contra between the implementation of online learning. The study aimed to find out the development of English Online Tasks and integrate those tasks in Online Learning Platforms. The study employed qualitative approach with interview and observation method. The sample of this study is one English teacher from SMA Negeri 4 Singaraja. The results showed that the English teacher has a lot of tasks during online learning in 1 semester. In developing English Online Tasks, the teacher has many methods. These tasks are integrated into several Online Learning Platforms. Therefore, it is suggested for the government to use this result as a reference to evaluate the online learning specifically in giving English Online Tasks for senior high school students.